Integrated flood countermeasures in the upper and middle Chao Phraya River Basin. Issue 2 (3rd April 2019) - Jamrussri, Sarawut; Toda, Yuji; Tsubaki, Ryota
Abstract : Flooding is a major natural hazard in the Chao Phraya River Basin (CPRB) because of its geography and the strong influence of seasonal monsoon rains. After the catastrophic flood of 2011, Thailand has not developed any major flood defenses, except for emergency measures. To minimize fatalities and economic losses, integrated flood countermeasures are necessary for flood control in the CPRB. A consideration of the widest possible set of flood countermeasures is needed to develop new alternatives that provide the information for overcoming severe flooding. The objectives of this study are (1) to investigate whether integrated flood countermeasures in the upper and middle CPRB can overcome severe flood events, (2) to identify the best solution from a set of flood countermeasures for each severe flood event, and (3) to explore the optimal operation of retention areas and dams for sustainable flood management in the upper and middle CPRB.